The impact of stress on the behavior of C57BL/6 mice with liver injury: a comparative study - Mușat, Mădălina Iuliana; Mitran, Smaranda Ioana; Udriștoiu, Ion; Albu, Carmen Valeria; Cătălin, Bogdan (Frontiers in Behavioral Neuroscience, 2024)
Introduction: Depressive-like behavior has been shown to be associated with liver damage. This study aimed to evaluate the impact of three different models of depression on the behavior of mice with liver injury. Methods: During the 4 weeks of methionine/choline deficiency diet (MCD), adult C57BL/6 mice were randomly divided into four groups: MCD (no stress protocol, n=6), chronic unpredictable mild stress (CUMS, n = 9), acute and repeated forced swim stress (aFSS (n=9) and rFSS (n=9)). Results: All depression protocols induced increased anhedonia and anxiety-like behavior compared to baseline and had no impact on the severity of liver damage, according to ultrasonography. However, different protocols evoked different overall behavior patterns. After the depressive-like behavior induction protocols, animals subjected to aFSS did not exhibit anxiety-like behavior differences compared to MCD animals, while mice subjected to CUMS showed additional weight loss compared to FSS animals. All tested protocols for inducing depressive-like behavior decreased the short-term memory of mice with liver damage, as assessed by the novel object recognition test (NORT). Discussion: Our results show that the use of all protocols seems to generate different levels of anxiety-like behavior, but only the depressive-like behavior induction procedures associate additional anhedonia and memory impairment in mice with liver injury.